Using Sounds for Propaganda in the Sarit–Thanom Government Era, 1960s - Rungruangtantisuk , Thanawat (Journal of Letters, 2026)
This article proposes that since sounds are related to human perception, they can be tool of government for propaganda. In the context of Thai society, the use of sounds for propaganda in the Sarit–Thanom government era deserves attention because these sounds continue to circulate and be reproduced in the present day. A study of the history of sounds and propaganda under the Sarit–Thanom governments in the 1960s shows that advances in sound dissemination systems – which have developments from the previous decade - enabled the government to use sound effectively for leading people in the Cold War situation. Both Field Marshal Sarit Thanarat’s sound in radio broadcasts and the sounds in propaganda films. Moreover, sounds could be chosen and adapted to align with the government’s objectives, especially sounds in war, which had an impact on security. Ultimately, these sounds have remained embedded and continue to reverberate in the auditory nerve of Thai society.